Relational Thinking And Problem Solution Strategies Beginning Algebra High School Students - Pandapotan Nainggolan, Sahat (Journal of World Science, 2022)
Many students' difficulties in learning early algebra are associated with deficiencies in learning during the student's transition from arithmetic to algebra. relational thinking; a way of thinking that can be a gateway to algebraic thinking, is touted as one of the solutions to these difficulties. This study aims to determine the profile of relational thinking and early algebra problem solving strategies for junior high school students. Through the phenomenological design, the researcher selected six participants who fit the research criteria. The data analyzed refers to several theoretical frameworks on relational thinking from several experts. This study focuses on the indicators of interpreting the equals sign , using the relationship between numbers and applying the basic properties of number operations, as well as the methods students use in solving initial algebraic problems (algebraic forms and linear equations of one variable). As a result and its implication, students' relational thinking is seen in several items, namely the first 3 indicator items: each item is seen in S1, S4, and S6; The second 2 indicator items are visible on the S4; and the third 3 indicator items are seen in S1. The majority of subjects do computing dominantly and or apply the nature of operations based on procedural knowledge. Similarly, in solving early algebra problems, it was found that the dominant tendency of students to consider algebraic expressions from a procedural perspective rather than a structural perspective (based on mathematical concepts or structures). From these results, it is deemed necessary to develop relational thinking since students study arithmetic in elementary school, including by familiarizing students with number sentences in various forms and encouraging understanding of mathematical structures (relationships between elements and understanding of the nature of number operations).